2015
DOI: 10.1111/jsap.12366
|View full text |Cite
|
Sign up to set email alerts
|

Pneumopericardium, pneumomediastinum, pneumothorax and pneumoretroperitoneum complicating pulmonary metastatic carcinoma in a cat

Abstract: This report describes a case of severe spontaneous tension pneumopericardium with concurrent pneumomediastinum, pneumothorax and retropneumoperitoneum in a cat presenting with dyspnoea and signs of cardiac tamponade secondary to metastatic pulmonary carcinoma. Spontaneous pneumopericardium is an extremely uncommon condition consisting of pericardial gas in the absence of iatrogenic/traumatic causes. In humans, it has been described secondary to pneumonia or lung abscess and very rarely secondary to pulmonary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, there are two cases with cardiac tamponade symptoms due to pneumopericardium, but the animals finally died. 2,3 In our case, the dog had no clinical signs related to pneumopericardium. It is known that a gradual increase of air within the pericardial sac may prevent the development of serious signs of cardiac tamponade.…”
Section: Learning Points/take-home Messagesmentioning
confidence: 50%
See 3 more Smart Citations
“…However, there are two cases with cardiac tamponade symptoms due to pneumopericardium, but the animals finally died. 2,3 In our case, the dog had no clinical signs related to pneumopericardium. It is known that a gradual increase of air within the pericardial sac may prevent the development of serious signs of cardiac tamponade.…”
Section: Learning Points/take-home Messagesmentioning
confidence: 50%
“…CT has also been used for diagnosis of pneumopericardium, both in small animals and humans, aiding in the diagnosis in complicated cases of concurrent pneumomediastinum, pneumothorax and pneumopericardium. 1,2,16 It has also been reported that pneumopericardium in humans is frequently a misdiagnosed pneumomediastinum and in such cases CT is the diagnostic tool of choice leading to the final diagnosis. 30 In our dog, CT was not performed because of financial constraints of the owners.…”
Section: Learning Points/take-home Messagesmentioning
confidence: 99%
See 2 more Smart Citations
“…In cats, pneumoperitoneum has been reported to occur secondary to metastatic pulmonary carcinoma (Greci et al., 2015 ), while it may occur secondary to blunt force trauma to the chest in dogs (Simmonds et al., 2011 ). In dogs and cats, trauma‐induced (36%) and spontaneous (64%) pneumoperitoneum, caused by perforation of hollow viscus and pneumothorax, are the most common causes of pneumoperitoneum (Saunders & Tobias, 2003 ).…”
Section: Introductionmentioning
confidence: 99%